Absence of the Min System Does Not Cause Major Cell Division Defects in Agrobacterium tumefaciens - Flores, Sue A.; Howell, Matthew; Daniel, Jeremy J.; Piccolo, Rebecca; Brown, Pamela J. B. (Frontiers in Microbiology, 2018)
In A. tumefaciens, the essential FtsZ protein is located at the growth pole before shifting to the mid-cell right before division. Loss of FtsZ causes a halt in cell separation and lysis of cells. To understand how FtsZ polymerization is regulated to properly localize the FtsZ ring at the mid-cell, we have conducted a systematic characterization of the Min system in A. tumefaciens. Our findings indicate that the Min system is not required for cell survival. Yet, we find that the deletion of either minE or minCDE results in a broad cell size distribution, including an increase in the proportion of short and long cells. We observe that the site of constriction is misplaced in the minE or minCDE deletion strains allowing for short cells to arise from sites of constriction near the cell poles. Remarkably, the short cells are viable and contain DNA. In order to observe chromosome replication and segregation in these strains, YFP-ParB is used as a proxy to track the origin of replication as cells elongate and divide. In the absence of the Min proteins, duplication and segregation of the origin of replication is frequently delayed. Taken together, our data suggest that the Min system contributes to the proper regulation of FtsZ placement and subsequent cell division. Furthermore, the failure to precisely place FtsZ rings at mid-cell in the min mutants impacts other cell cycle features including chromosome segregation.